ROLE OF SOCIO-DEMOGRAPHY, LIFESTYLE AND COMPLEMENTARY AND ALTERNATIVE MEDICINE (CAM) ON COGNITION IN PARKINSON DISEASE (PD) – A CROSS- SECTIONAL STUDY - Basanta Kumar Mohanty; Pan Jia Hui; Bernadatte Jawai Lawrence; Muhd. Nazri b. Abd Majid; Muhd. Fauzan b. Moktar (Asian Journal of Medicine & Health Sciences, 2020)
Objective: To study the role of socio-demography, lifestyle factors and the usage of complementary and alternative medicine (CAM) on cognition in Parkinson’s disease. (PD) The study was an observational, cross sectional study and was conducted at Perak Parkinson’s Association Centre (PPA) and neurology clinic of Hospital Raja Permaisuri Bainun (HRPB). A total of 51 patients, 14 patients from PPA and 37 patients from HRPB who were diagnosed with PD were included in the study. Patients were tested by Mini-Mental State Examination (MMSE) and face to face interview using a structured questionnaire. Results: Patients who were in younger age group (< 60 years old) had better MMSE score compared to others (p=0.07). Those who attained at least secondary level of education were found to be at lower risk of cognitive impairment (p=0.047). Those with younger age of onset of PD (2044 years old) had less risk of cognitive impairment (p=0.048). Duration of PD (p=0.040), use of traditional Chinese medicine (TCM) (p=0.009) and practice of Tai Chi (p=0.04) also had significant association with cognition. Conclusion: Higher education level, younger age group, younger age of onset, duration of PD, use of TCM and practice of Tai Chi has significant association with cognition in PD patients. Further studies are needed to corroborate our findings.